2015
DOI: 10.1002/bmc.3447
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sparstolonin B by ultra‐high performance liquid chromatography coupled with triple quadrupole mass spectrometry: application to pharmacokinetic study of sparstolonin B in rat plasma

Abstract: Sparstolonin B (SsnB), a spontaneous isocoumarin compound isolated from the tuber of Scirpus yagara Ohwi. (Cyperaceae), possesses potent anti-inflammatory and antitumor activity. In the present study, a rapid and simple UHPLC/MS/MS method for determination of SsnB in rat plasma was developed and validated. Plasma samples were pretreated by liquid-liquid extraction with ethyl acetate containing rhein as an internal standard and separated on a C18 column at 35 °C, with a gradient mobile phase consisting of aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A previous study demonstrated that sparstolonin B is a low-toxicity TLR2 and TLR4-selective antagonist, which is able to inhibit inflammation induced by lipopolysaccharide in in vivo mouse models (16). Therefore, sparstolonin B has been hypothesized to be a potential novel treatment for inflammation and associated diseases (17). In the present study, the potential protective effect of sparstolonin B against inflammation and apoptosis in an SCI model was examined, and the molecular mechanism underlying the effects of sparstolonin B in SCI was investigated by studying alterations in TLR4 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that sparstolonin B is a low-toxicity TLR2 and TLR4-selective antagonist, which is able to inhibit inflammation induced by lipopolysaccharide in in vivo mouse models (16). Therefore, sparstolonin B has been hypothesized to be a potential novel treatment for inflammation and associated diseases (17). In the present study, the potential protective effect of sparstolonin B against inflammation and apoptosis in an SCI model was examined, and the molecular mechanism underlying the effects of sparstolonin B in SCI was investigated by studying alterations in TLR4 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%